Cornflour Substitute Onion Sticks: Physical and Sensory Quality - Adinda Mutiara Dewi; Nur Riska; Rusilanti Rusilanti (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This research aims to examine the effect of corn flour (Zea mays L.) substitution on the physical and sensory qualities of onion sticks as an alternative to partially replacing wheat flour. The study was carried out experimentally with three levels of corn flour substitution: 20%, 30%, and 40%. Physical tests included expansion power, thickness, and crispness; while sensory evaluation assessed color, aroma, taste, texture, and thickness. ANOVA test results showed significant effects on expansion power, thickness, and crispness. The Kruskal- Wallis test revealed that the level of corn flour substitution significantly affected thickness, while color, margarine aroma, savory taste, corn flavor, and texture were not significantly influenced. The Tukey test indicated that 20% substitution produced the best thickness quality. These findings suggest that corn flour substitution up to 20% can produce onion sticks with good physical and sensory quality, and support food diversification efforts based on local ingredients to reduce dependence on imported wheat flour.